LIBRARY SELF SERVICE SYSTEM USING NFC AND 2FA GOOGLE AUTHENTICATOR - Mychael Maoeretz Engel; Henry David Lie (Jurnal Teknik Informatika (Jutif), 2022)
The implementation of a self-service system is already used by many libraries, mainly on self-loan books. Self-service generally only uses RFID as a medium for identifying members and borrowed books, but using RFID alone as the head of the identification process may lead to many crimes such as using someone else's member card to borrow books, scam, and so on. This study aims to propose a new business process for self loan books from the library by combining NFC or RFID technology and 2FA (two-factor authentication) to minimize the crimes such as fraudulence, scams, and so on. The results showed that the system or prototype could work and function properly. The process of reading NFC tags and the use of 2F also runs quickly and safely.